Fallacies of "hypoxic training" in swimming - Craig, A. B. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
People who do repetitive breath-hold diving can increase their time underwater with practice (Schaefer, 1955; Hong et al., 1970). It has been assumed that this increased time is related to an individual's responses to repeated hypoxia. It is further reasoned that one of the features of an adaptation to repeated hypoxia might be in increase in one's anaerobic capacity. These arguments are not new. Most recently Counsilman (1975) and Vasar and Laidre (1975) have suggested that "hypoxic" methods oftraining swimmers might be useful despite the strong warning that such techniques might be dangerous (Craig, Jr., 1961a; Lanphier and Rahn, 1963a, b; Craig, Jr., 1976). It is interesting that many swimming coaches in the Rochester, N.Y. area have accepted Counsilman's (1975) suggestions and use many variations of so-called "hypoxic training." The present investigation was designed to simulate the effects of varying the breathing frequency during swimming. The experiments were compared with previous work (Craig, Jr., and Harley, 1968; Craig, Jr., and Medd, 1968a, b), which indicated that the limitations of repetitive breath holds without prior hyperventilation were related primarily to the increase of the partial pressure of carbon dioxide (Pco2), and hypoxia had relatively little influence.